2009
DOI: 10.1074/jbc.m109.023861
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Lysine Acetyltransferase KAT3B/p300 Activity by a Naturally Occurring Hydroxynaphthoquinone, Plumbagin

Abstract: Lysine acetyltransferases (KATs), p300 (KAT3B), and its close homologue CREB-binding protein (KAT3A) are probably the most widely studied KATs with well documented roles in various cellular processes. Hence, the dysfunction of p300 may result in the dysregulation of gene expression leading to the manifestation of many disorders. The acetyltransferase activity of p300/CREB-binding protein is therefore considered as a target for new generation therapeutics. We describe here a natural compound, plumbagin (RTK1), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
102
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 113 publications
(106 citation statements)
references
References 35 publications
(36 reference statements)
4
102
0
Order By: Relevance
“…5D) (Choi et al 2009), and plumbagin ( Fig. 5E) (Ravindra et al 2009 Some high-throughput screens have been reported, identifying HAT inhibitors with similarly modest potencies to the compounds discussed in the previous paragraph. The high-throughput screening of a 70,000 compound library yielded a family of isothiazolones (CCT077791 and CCT077792) as PCAF inhibitors that were subsequently derivatized as low micromolar PCAF and p300 inhibitors ( Fig.…”
Section: Writers and Readers Of Histone Acetylationmentioning
confidence: 99%
“…5D) (Choi et al 2009), and plumbagin ( Fig. 5E) (Ravindra et al 2009 Some high-throughput screens have been reported, identifying HAT inhibitors with similarly modest potencies to the compounds discussed in the previous paragraph. The high-throughput screening of a 70,000 compound library yielded a family of isothiazolones (CCT077791 and CCT077792) as PCAF inhibitors that were subsequently derivatized as low micromolar PCAF and p300 inhibitors ( Fig.…”
Section: Writers and Readers Of Histone Acetylationmentioning
confidence: 99%
“…However, the role of curcumin as an acetyltransferase inhibitor has not been investigated in that study. Another example with p300/CBP HAT inhibiting abilities is plumbagin (43), which induces apoptosis and inhibits invasion of prostate cancer cells by several mechanisms including blocking of DNA-binding ability of NF-kB (44). Again, in this context, the role of plumbagin as acetyltransferase inhibitor was not analyzed.…”
Section: Potential Of Chemical P300 Inhibitionmentioning
confidence: 99%
“…Plumbagin is another agent, derived from Plumbago rosea root extract, that has been found to potently inhibit HAT activity (Ravindra et al 2009). Plumbagin derivatives without a hydroxyl group lost HAT inhibitory activity, indicating that the hydroxyl group is required for this activity.…”
Section: Effect Of Other Natural Compounds On Epigeneticsmentioning
confidence: 99%